The impact of generation Z intent to purchase housing property in Klang valley - Teoh, Kee Keat (2022)
This research is aiming to study the impact of generation Z when they intent to purchase housing property in the area of Klang Valley. This research will help not only researchers to understand perception toward generation Z purchasing behaviour but also help those people who are confusing on purchase or rent a housing property will be the suitable decision for themselves. The research will be done with a quantitative method and then results will be analysed and studied carefully. This research will also help to acknowledge underlying problems that may have not been known before this.